Pengaruh Disiplin Kerja, Lingkungan Kerja, Pengawasan Kerja, Pelatihan Dan Pembinaan Terhadap Kinerja Kerja Pegawai Pada Dinas Pendidikan Labuhanbatu Utara - Nurcahaya, Nurcahaya (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the work discipline, work environment, work supervision, training and coaching positive and significant effect on the work performance of employees at the North Labuhanbatu Education Office. This Type Of Research Is Associative Research. Data collection in this study was conducted through a survey approach with a type of quantitative descriptive research by distributing questionnaires to 30 respondents, namely employees at the North Labuhanbatu Education Office. Data analysis techniques in this study are descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significant Test (t test), simultaneous significant test (F test), and determination coefficient test (R2). Â The results of this study showed that partially (t test) is known that the work discipline has a positive and significant effect on the work performance of employees at the North Labuhanbatu Education Office with a value of thitung (4.937) > ttable (1.713) and the significance level of 0.000 < 0.05. The work environment has a positive and significant effect on the work performance of employees at the North Labuhanbatu Education Office with the value of thitung (4.667) > ttable (1.713) and the significance level of 0.000< 0.05. Supervision of work has a positive and significant effect on the work performance of employees at the North Labuhanbatu Education Office with a value of thitung (3.919) > ttable (1.713) and the significance level of 0.001 < 0.05. Training has a positive and significant effect on employee performance at the North Labuhanbatu Education Office with the value of thitung (4.257) > ttable (1.713) and the significance level of 0.000 < 0.05. Then coaching positive and significant effect on the performance of employees at the Department of Education Labuhanbatu Utara with the value of thitung is (4.766) > ttable (1.713) and the level of significance 0.000 < 0.05. Â In simultaneous testing (test F) known that the work discipline, work environment, work supervision, training and coaching positive and significant effect on the work performance of employees at the Department of Education North Labuhanbatu with the results showed that the value of Fhitung is (19.098) > Ftable (2.62) and the level of significance 0.00 < 0.05. Through testing the coefficient of determination Adjusted R Square is equal to 0.757. This value means that work performance is able to be explained by work discipline, work environment, work supervision, training and coaching by 75.7%. While the remaining 24.3% influenced by other variables that are not studied in this study.